Lithium composite negative electrode with tab and lithium battery comprising lithium composite negative electrode
By designing a lithium composite negative electrode with its own electrode ears in a lithium-ion battery, and using a carbonaceous membrane material as a current collector membrane material, the problem that cannot be solved in the existing technology is solved, and the battery capacity and specific energy are improved.
Patent Information
- Application Number
- CN202420287569.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2034-02-07
AI Technical Summary
In existing lithium-ion batteries, carbonaceous film or other flexible conductive film cannot be used directly as electrodes after composite metal lithium negative electrodes, resulting in the problems caused by electrodes that cannot be solved.
A lithium composite negative electrode with its own electrode is designed. By combining two negative electrode layers on both sides of the current collector-elbow composite structure, the overlapping area between the current collector and the electrode is maintained. Carbonaceous film materials or other flexible conductive film materials are used as the current collector film materials to replace the high-density copper foil current collector.
The capacity of lithium-ion batteries is increased by about 5%, with a specific energy of more than 400wh/kg, and the extreme ear problem caused by current collector film materials in industrial production is solved.
Smart Images

Figure CN222637305U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of electrochemical energy storage, in particular to a lithium composite negative electrode for a lithium ion battery. Background Art
[0002] As society's requirements for the energy density of lithium-ion batteries are getting higher and higher, the current research direction is turning to negative electrode materials with higher specific capacity. Metallic lithium is considered to be the best negative electrode material due to its capacity of 3860mAh / g and low potential of -3.04V. Secondly, to increase the energy density of the battery, it is necessary to reduce the proportion of inactive substances. For the current collector, the weight of the current collector copper foil can be reduced by continuously thinning the thickness of the copper current collector, but the density of metallic copper is 8.96g / cm 3 , the thinnest copper foil is 4um thick (4um thick copper foil is easy to break), which is equivalent to 67um thick lithium metal. Currently, carbon film materials with certain conductivity or other flexible conductive film materials are being developed to replace the current collector copper foil. The density of carbon film materials is 1g / cm 3 It can be a good substitute for the traditional current collector. There is no problem in using carbonaceous film materials or other flexible conductive film materials as current collector materials. The current problem is that after the relevant film materials are composited with metal lithium negative electrode, the carbonaceous film materials or other conductive film materials cannot be directly used as tabs, and the problems caused by the tabs cannot be solved. Utility Model Content
[0003] In view of the above problems, the utility model prepares a lithium composite negative electrode with its own pole ear. The current collector film material is a carbon film material or other flexible conductive film material. After the low-density current collector film replaces the high-density copper foil current collector, the battery capacity is increased by about 5%, and the battery's specific energy can be higher than 400wh / kg.
[0004] The utility model adopts the following technical solutions:
[0005] A lithium composite negative electrode with a self-contained tab, the lithium composite electrode comprising: two upper and lower negative electrode layers; a current collector sandwiched between the two negative electrode layers; and a tab joined to the current collector via an overlap region, the overlap region consisting of an overlapping portion of the current collector and the tab, also located between the upper and lower negative electrode layers, the non-overlapping portion of the tab extending beyond the edge of the negative electrode layer.
[0006] In certain embodiments, the width of the overlapping region is 0-5 mm.
[0007] In certain embodiments, the negative electrode layer is a metallic lithium layer or a lithium alloy layer.
[0008] In some embodiments, the current collector film material is a carbonaceous film material or other flexible conductive film materials.
[0009] In some embodiments, the tab is made of metal foil.
[0010] In some embodiments, the negative electrode layer has a thickness of 1-100 um and a width of 50-1400 mm.
[0011] In some embodiments, the thickness of the current collector is 5-50 um.
[0012] In certain embodiments, the width of the current collector is smaller than that of the negative electrode layer, and one end of the current collector is aligned with the negative electrode layer in the width direction.
[0013] In certain embodiments, the tab has the same thickness as the current collector.
[0014] In certain embodiments, the total width of the current collector and the tab is greater than the width of the negative electrode layer.
[0015] In certain embodiments, one side of the current collector and / or one side of the tab has a mark for guiding the current collector and the tab to form an overlapping area, and the mark includes a mark line formed by multiple small holes arranged along the edge of the current collector or the tab.
[0016] The utility model also provides a lithium battery, which comprises the above-mentioned lithium composite negative electrode with its own pole ear.
[0017] The utility model has at least one of the following advantages:
[0018] (1) The lithium composite negative electrode with a tab of the utility model is composited with two negative electrode layers on both sides of the current collector-tab composite structure, so that the overlap area between the current collector and the tab is maintained, thereby solving the problem of the current collector film material
[0019] (Except for metal current collectors) Industrial production applications raise the issue of tabs.
[0020] (2) The lithium composite negative electrode with its own tab of the utility model has great advantages in the application of high specific energy batteries because the density of the current collector film material is much smaller than that of copper foil.
[0021] (3) The production process of the lithium composite negative electrode with its own tabs of the utility model is mature and can be applied in large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a structural schematic diagram of the lithium composite electrode of the utility model.
[0023] Figure 2 This is another schematic diagram of the structure of the lithium composite electrode of the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the utility model more clear, the specific implementation of the utility model is further described in detail below with reference to the accompanying drawings. It should be understood that the technical features involved in each implementation of the utility model described below can be combined with each other as long as they do not conflict with each other.
[0025] One aspect of the present invention provides a lithium composite electrode with a self-contained tab, the lithium composite electrode comprising:
[0026] Two negative electrode layers: upper and lower;
[0027] a current collector sandwiched between two negative electrode layers; and
[0028] The tab is connected to the current collector through an overlapping area, wherein the overlapping area is composed of the overlapping portion of the current collector and the tab and is also located between the upper and lower negative electrode layers, and the non-overlapping portion of the tab extends beyond the edge of the negative electrode layer.
[0029] Figure 1 and Figure 2 The schematic diagram of the structure of the lithium composite electrode of the utility model is shown, wherein the lithium composite electrode has two negative electrode layers 1, a current collector 2 sandwiched between the two negative electrode layers, and a pole ear 3 overlapped with the current collector 2. Figure 1 shows the structure when the width of the overlap area is 0, Figure 2 The structure is shown when the width of the overlapping region 4 is greater than 0.
[0030] In the utility model, active material metal lithium and lithium alloy are selected as the material of the negative electrode layer, the current collector is selected from carbon film material or other flexible conductive film material, and the lead-out tab is selected from metal foil material; one side edge of the current collector film material and one side edge of the lead-out tab overlap by 0-5mm, and the metal foil area without lithium composite is used as the tab.
[0031] According to one embodiment, the active material is distributed to the current collector carbon film material and the lead-out tab area through coating, pressure compounding, and vapor deposition processes to obtain a lithium composite negative electrode with tabs on both sides.
[0032] According to one embodiment, the thickness of the active material metal lithium or lithium alloy (thickness of the negative electrode layer) is 1-100 um, preferably 1-20 um; the width is 50-1400 mm, preferably 200-700 mm.
[0033] According to one embodiment, the lithium alloy is formed by a combination of metallic lithium and any one or at least two elements of Ag, Au, Sn, Si, Zn, Al, Mg, In, Ga, B, Mn, Sb, Cr, C, V, Cu, Fe or Ti.
[0034] According to one embodiment, the thickness of the current collector is 5-50 um, preferably 5-20 um.
[0035] According to one embodiment, the tab is made of metal foil, including copper foil, nickel foil, and stainless steel foil; the thickness of the metal conductive foil is 5-50um, preferably 5-20um, and the thickness of the tab matches or is consistent with the thickness of the current collector film.
[0036] According to one embodiment, the lithium composite negative electrode with its own tab may be in the form of a continuous web (rolled).
[0037] The lithium composite electrode of the utility model can be prepared by the following method, which comprises:
[0038] Unwinding the upper and lower rolls of lithium metal strips or lithium alloy strips at the same time, unwinding the conductive carbon film material and the conductive metal foil material in the middle at the same time, the thickness of the carbon film material and the metal foil material are consistent, and the unwinding speed of the carbon film material, the metal foil and the lithium metal strip or lithium alloy strip is consistent, the unwinding speed is 5-50 m / min;
[0039] The upper and lower rolls of metal lithium strips or lithium alloy strips, the carbon film material and the metal foil material in the middle overlap by 0-5mm, and are pressure-compounded to obtain a composite negative electrode with its own tabs.
[0040] Another aspect of the utility model provides the use of the composite negative electrode with a self-contained tab in a lithium-ion battery.
[0041] According to one embodiment, the utility model provides a lithium battery, which includes the above-mentioned lithium composite negative electrode, and the positive electrode material is selected from ternary nickel-cobalt-manganese material, ternary nickel-cobalt-aluminum material, lithium-rich manganese-based positive electrode material, lithium cobalt oxide, lithium iron phosphate, and sulfur-based positive electrode material.
[0042] According to one embodiment, the electrolyte of the lithium battery can be selected from a liquid electrolyte or a solid electrolyte; the liquid electrolyte can be selected from an ester or an ether; the solid electrolyte can be selected from an oxide solid electrolyte, a halide solid electrolyte, a sulfide solid electrolyte or a polymer electrolyte, such as a polyethylene oxide (mixed oxide, halide or sulfide powder) electrolyte.
[0043] For liquid batteries, the diaphragm is made of polypropylene (PP), polyethylene (PE) or a PP and PE laminated diaphragm, and the diaphragm can be coated with ceramic or polyvinylidene fluoride.
[0044] The battery can be made into square, soft pack and cylindrical batteries.
[0045] The present invention is illustrated below by way of examples. The various product structural parameters, various reaction participants and process conditions used in the following examples are all relatively typical examples. However, after a large number of experiments and verifications by the inventor of this case, other different structural parameters, other types of reaction participants and other process conditions listed above are also applicable and can also achieve the technical effects claimed in this utility model.
[0046] Example 1
[0047] Two rolls of lithium metal tape are unwound at the same time, the thickness of the lithium tape is 20um, and the carbon nanotube film (thickness 8um) of the current collector film in the middle position and the copper foil (thickness 8um) of the lead-out tab are unwound at the same time. The width of the carbon nanotube film is 100mm, the width of the copper foil is 15mm, and the width of the lithium tape is 102mm. The edge of one side of the carbon nanotube film and the edge of one side of the copper foil are close together, and the overlapping area is 0mm; the unwinding speed of the carbon nanotube film, copper foil and lithium metal tape is consistent, the unwinding speed is 6 meters / min, and the three layers of tape are pressure-compounded to obtain a lithium composite negative electrode with its own tabs.
[0048] Example 2
[0049] At the same time, two rolls of lithium-magnesium alloy strips (magnesium content is 10%) are unwound, and the thickness of the lithium alloy strip is 20um. At the same time, the current collector graphite film (thickness 15um) in the middle position and the metal foil copper foil (thickness 15um) for lead-out tabs are unwound. The width of the graphite film is 100mm, the width of the copper foil is 15mm, and the width of the lithium-magnesium alloy strip is 102mm. The edge of one side of the graphite film and the edge of one side of the copper foil overlap together, the overlapping area is 2mm, and the thickness of the overlapping area is 17um thicker than the thickness of the non-overlapping area. The unwinding speed of the graphite film, copper foil and lithium-magnesium alloy strip is consistent, and the unwinding speed is 10 meters / min. The three-layer strip is pressure-compounded to obtain a lithium composite negative electrode with its own tabs.
[0050] Comparative Example 1:
[0051] Two rolls of metal lithium ribbon are unwound at the same time, the thickness of the lithium ribbon is 20um, and the current collector copper foil (thickness 8um) in the middle position is unwound at the same time, the width of the copper foil is 115mm, and the width of the lithium ribbon is 102mm. The unwinding speed of the copper foil and the metal lithium ribbon is the same, the unwinding speed is 8 meters / min, and the three layers of strips are pressure-compounded to obtain a lithium composite negative electrode with copper foil tabs.
[0052] Example 3: The negative electrode uses the lithium composite negative electrode prepared in Example 1, and the positive electrode uses NCM (811 nickel-cobalt-manganese ternary positive electrode), and the coating surface density is 52 mg / cm 2The positive electrode sheet area is 43*56mm, the negative electrode sheet area is 45*58mm, the diaphragm is made of PE material, and the soft pack battery with 4 positive and 5 negative is assembled. The electrolyte is 1M LiPF 6 , EC (ethylene carbonate): EMC (ethyl methyl carbonate) = 3:7 (vol / vol). The negative electrode sheet, NCM ternary positive electrode sheet and separator are assembled into a soft pack battery with the help of a laminating machine. The test voltage range is 2.8-4.4V, the charging current is 0.1C, and the discharge current is 0.5C.
[0053] Example 4: The negative electrode used was the lithium composite negative electrode prepared in Example 2, and the assembly of the positive electrode, separator, electrolyte and soft-pack battery was the same as in Example 3.
[0054] Comparative Example 2: The negative electrode used was the lithium composite negative electrode of Comparative Example 1, and the assembly of the positive electrode, separator, electrolyte and soft-pack battery was the same as that of Example 3.
[0055] Table 1 Comparison of battery cell specific energy data
[0056] Group Specific energy of battery cell (wh / kg) Number of cycles (capacity decay 80%) Example 3 425.6 126 Example 4 421.7 138 Comparative Example 2 398.8 102
[0057] It can be seen from Table 1 that the specific energy of the battery cell using copper foil as the current collector is the lowest at 398.8wh / kg, because copper has a high specific gravity; Examples 3 and 4 use carbon film materials as current collectors, and because the current collectors are light in weight, the specific energy of the battery cell can be increased by about 5%; the cycle performance of Example 4 is better than that of Example 3, because magnesium in the lithium-magnesium alloy is a good deposition site, and the presence of magnesium is conducive to the uniform deposition of metallic lithium.
[0058] It should be understood that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium composite negative electrode with a self-contained tab, characterized in that: The lithium composite negative electrode comprises: Two negative electrode layers: upper and lower; a current collector sandwiched between two negative electrode layers; and The tab is connected to the current collector through an overlapping area, wherein the overlapping area is composed of the overlapping portion of the current collector and the tab and is also located between the upper and lower negative electrode layers, and the non-overlapping portion of the tab extends beyond the edge of the negative electrode layer.
2. The lithium composite negative electrode with a self-contained tab according to claim 1, characterized in that: The width of the overlapping area is 0-5 mm.
3. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The negative electrode layer is a metal lithium layer or a lithium alloy layer.
4. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The thickness of the negative electrode layer is 1-100 um, and the width is 50-1400 mm.
5. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The thickness of the current collector is 5-50 um.
6. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The current collector has a width smaller than that of the negative electrode layer, and one end of the current collector is aligned with the negative electrode layer in the width direction.
7. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The tab has the same thickness as the current collector.
8. The lithium composite negative electrode with a self-contained tab according to claim 1, characterized in that: The total width of the current collector and the tab is greater than the width of the negative electrode layer.
9. The lithium composite negative electrode with a tab according to claim 1, characterized in that: One side of the current collector and / or one side of the pole lug has a mark for guiding the current collector and the pole lug to form an overlapping area, and the mark includes a mark line formed by multiple small holes arranged along the edge of the current collector or the pole lug.
10. A lithium battery, characterized in that: The lithium battery comprises the lithium composite negative electrode with a self-contained tab according to any one of claims 1 to 9.